Pengaruh Pengetahuan Pajak dan Sanksi Pajak Terhadap Kepatuhan Pajak UMKM di Kota Yogyakarta - Antonius Ardani Jampar; Suyanto (Jurnal Literasi Akuntansi, 2025)
Purpose: This study aims to examine the influence of tax knowledge and tax sanctions on tax compliance among MSMEs in Yogyakarta City. Method: The population in this study was all registered MSMEs in Yogyakarta City, with a sample of 106 respondents drawn using a purposive sampling technique. The research method used was a quantitative survey approach through questionnaire distribution. The data obtained were analyzed using multiple linear regression techniques. The data analysis method used was multiple linear regression analysis with SPSS version 25. Finding: The results show that tax knowledge and tax sanctions have a positive and significant effect on MSME tax compliance. Novelty: Understanding taxpayer compliance in the MSME sector in Yogyakarta City through empirical testing of the influence of tax knowledge and tax sanctions. This research has the potential to validate or modify the Theory of Planned Behavior (TPB) in the unique context of MSMEs in Yogyakarta.